1997
DOI: 10.1088/0953-8984/9/1/009
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the growth behaviour of gold film surfaces evaporation-deposited on mica under different conditions

Abstract: A systematic AFM study of gold films deposited on mica substrates under a range of selected conditions reveals the evolution of the surface morphology of the films as a function of growth temperature, film thickness, and deposition rate. Scaling analysis shows that the growth behaviour of the surfaces of these films can be considered as self-affine fractals. The observed topography follows island-type (3D) growth processes in the majority of cases with a roughness exponent, α, in the range 0.24-0.75, or quasi-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 35 publications
(50 reference statements)
3
28
0
Order By: Relevance
“…Previous work has also shown that single atoms are very mobile over the sur- face but growth can still nucleate without the need of a seed point (such as a surface defect) to which the mobile atoms can stick. 33 We also find that both single Ag atoms and Ag dimers are very mobile on the surface with energy barriers for diffusion of 0.12 eV and 0.22 eV, respectively. Surface trimers are also mobile and are found to diffuse as a unit with an energy barriers of 0.28 eV.…”
Section: A Deposition Of Silver Atoms On Silver Surfacesmentioning
confidence: 60%
“…Previous work has also shown that single atoms are very mobile over the sur- face but growth can still nucleate without the need of a seed point (such as a surface defect) to which the mobile atoms can stick. 33 We also find that both single Ag atoms and Ag dimers are very mobile on the surface with energy barriers for diffusion of 0.12 eV and 0.22 eV, respectively. Surface trimers are also mobile and are found to diffuse as a unit with an energy barriers of 0.28 eV.…”
Section: A Deposition Of Silver Atoms On Silver Surfacesmentioning
confidence: 60%
“…Alternatively, thermal annealing can enhance the flatness of the substrate and can markedly improve the grain size, reduce surface contamination, and afford highly oriented single crystal-like films 16 , without the need for heating during deposition. Annealing temperature and time seems not to contribute significantly to surface roughness when compared to other deposition factors 12,16,18 . However, annealing or heating of the substrate is not always feasible as it can lead to the generation of undesired stresses in the MEMS/NEMS device.…”
Section: Introductionmentioning
confidence: 81%
“…Studies showed that a deposition rate of less than 1 nm s -1 gives a smoother surface 14 , the chamber pressure (<10 -5 Torr) is insignificant compared to other factors 14,15 , the thickness of evaporated gold film has an effect on the size of the island, and [111] plateaus, with lateral dimensions in the range of 200 to 300 nm, occur for film thicknesses greater than 100 nm 17 . Moreover, studies reveal that the substrate temperature during deposition has a great influence on flatness and size of deposited gold grains 12,14,15,18,19 . By increasing the substrate temperature during deposition, adatoms and surface atoms are in a higher energy state compared to unheated substrate 18 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12,13 This hypothesis was based on the analysis of X-ray diffraction data and surface roughness data recorded with a scanning tunneling microscope (STM) on some metallic films. Measurements of the roughness of the surface of gold films evaporated onto mica substrates employing an atomic force microscope (AFM), 14 and of the roughness of gold films evaporated onto glass substrates performed with an STM 15,16 confirmed this assumption in the case of gold films. This may have stimulated theoretical efforts that gave rise to two theories that predict the increase in resistivity arising from electron-scattering by a rough fractal surface.…”
Section: Introductionmentioning
confidence: 88%